Communication Strategy To Preserve Gendruwon Ayon-Ayon Folk Arts In Local Wisdom-Based Acculturation In Tuban Regency - Kristin Tri Lestari (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2024)
Tuban is known as an area that has given birth to many folk arts, where the culture born from the people has a very strong and deep-rooted character. One of the legendary folk arts to this day is Gendruwon Ayon-ayon. Gendruwon Ayon-ayon is a traditional art that is also interspersed with jaranan dance. It is said that Gendruwon Ayon-ayon was brought by a cultural and artistic figure from Blora, Central Java. Gendruwon Ayon-ayon is not a native folk art from Tuban, but in Tuban, Gendruwon Ayon-ayon has experienced acculturation and presentation, Gendruwon Ayon-ayon is now interspersed with Reog. Therefore, it is very important to preserve this folk art so that it does not become extinct in the middle of modernization era through the right communication strategy. The purpose of this study is to determine the Communication Strategy for Preserving Gendruwon Ayon-Ayon Folk Art in Acculturation Based on Local Wisdom in Tuban Regency. In addition, it is also to determine the inhibiting and supporting factors. For key informants, we took Gendruwon Ayon-Ayon art activists because they are considered to be the most knowledgeable about this folk art. This study uses the Miles and Huberman Model data analysis technique, while the data validity technique is in the form of source triangulation, namely comparing or rechecking the degree of trustworthiness of information obtained from different sources.